Bacterial Conjunctivitis: An Updated Review for Healthcare Professionals - Alrawyah, Fahad Mohammed; Alqahtani, Mohammed Awadh Hussain; Alqahtani, Majed Abdullah Nasser; Alghamdi , Nour Hussain; Alfuhaigi, Noof Makrb; Alanzi, Fatmh Humoud; Aljasir, Luluh Yousef; Al Aldossary, Shaykhah Bdha; Aishaia, Fatmah Ibrahim; Alotaibi, Adel Sultan Obaid; Alotaibi, Majed Mohammad; Alotaibi, Abdulmajeed Mohammad; et al. (Journal of Ecohumanism, 2024)
Bacterial conjunctivitis, commonly known as "pink eye," is a prevalent ocular condition often diagnosed in primary healthcare settings. It is caused by bacterial infections, presenting symptoms like redness, itching, and discharge. While viral and allergic conjunctivitis are more common, bacterial conjunctivitis can lead to severe complications if left untreated. This review explores bacterial conjunctivitis’ etiology, epidemiology, pathophysiology, diagnosis, treatment, and complications, offering healthcare professionals insights for accurate management and diagnosis.The aim of this review is to update healthcare professionals on bacterial conjunctivitis, focusing on its causes, epidemiology, clinical features, diagnostic methods, and management strategies.This article synthesizes existing research on bacterial conjunctivitis, drawing from a range of sources to provide comprehensive insights into its transmission, pathogenesis, and the clinical approach to diagnosis and treatment. The review also examines bacterial pathogens, diagnostic tools, and antibiotic resistance patterns.Bacterial conjunctivitis is most commonly caused by Haemophilus influenzae, Streptococcus pneumoniae, and Staphylococcus aureus. In children, it is often linked to otitis media, while adults may experience more frequent cases of Staphylococcus aureus. The condition is diagnosed through clinical presentation, with occasional reliance on culture and PCR testing for complicated cases. Antibiotic treatment, particularly with topical agents, is effective in most cases, although overuse remains a concern. Empiric antibiotic therapy is often prescribed despite a relatively low bacterial infection rate in pediatric cases.Bacterial conjunctivitis is a common, treatable condition with a generally favorable prognosis. However, misdiagnosis and unnecessary antibiotic use contribute to the growing problem of antimicrobial resistance. Clinicians should adopt diagnostic approaches to minimize unnecessary prescriptions and enhance treatment efficacy.